NÆRING OG NYDELSE I ERNÆRINGSOPLYSNINGEN: Diskursiv regulering af mad- og spisevaner 1936-1985 - Christensen, Gudrun (Tidsskriftet Antropologi, 1998)
Gudrun Christensen: Nutrition and the Pleasures of Eating in Public Information Campaigns The article illustrates how the Agency of Consumer Affairs has tried to prevent specific diseases and to improve general health among the Danish population by changing nutritional practices. The study is a discourse analysis inspired by Michel Foucault, based on leaflets published between 1936 and 1985 in Denmark. The article focuses on how relations between nutrition and the pleasure of eating are constructed and shows how the societal understanding of nutritional problems has changed. Earlier on, the leaflets focused on deficiency, diseases and the improvement of public health as a means of simple survival and basic health in the Danish population. Fifty years later the leaflets discuss the prevention of specific food related diseases, such as coronary heart-disease and obesity, which are seen as a central element of modem lifestyle. The article shows how an attempt has been made to place scientifically based and rational forms of sense at the centre of everyday life with food and nutrition. In this process there is no longer room for food habits based on tradition, the pleasure for food, preferences of taste or food habits based on certain culinary preferences.